The role of clinical psychologist in speech and hearing clinic - Bharath Raj J (Journal of All India Institute of Speech and Hearing, 1970)
The idea of application of Clinical Psychology in the speech and hearing set up, first came to my mind about 3 years ago, when the Department of Clinical Psychology had to be started afresh at the All India Institute of Speech and  Hear- ing,  Mysore.   The  departmental work  had  to  be  geared to  the  needs  of the speech and hearing clinic